(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To analyze factors associated with the utilization of home-based medical testing services among residents in selected wards of Bac Tu Liem District, Hanoi, during the 2023–2024 period. Methods: A cross-sectional descriptive study was conducted from November 2023 to August 2024, involving 426 residents aged 18–70 years in Duc Thang, Dong Ngac, and Co Nhue 2 wards. Data were analyzed using SPSS 20.0 software. Univariable analysis, Chi-square tests, and crude Odds Ratios (cOR) were employed to identify significant associations. Results: Socio-economic and demographic characteristics played a significant role in driving the demand for on-site medical services (p < 0.05). Individuals in the high-income group (>10 million VND/month) had a 2.17 times higher likelihood of actual service utilization compared to the other groups. The demand was primarily concentrated among females, those of working age (18–45 years), and civil servants, with cOR values ranging from 2.26 to 3.02. The study also recorded that healthy individuals had more than double the odds of desiring service use compared to patients with chronic conditions (cOR = 2.11). Notably, willingness to pay at a higher price range (1,500,000–2,000,000 VND) was positively correlated with the level of desire for service utilization (cOR = 7.70). Conclusions: Community demand for mobile medical services is closely linked to internal individual factors and household economic contexts.